COMPARATIVE EVALUATION OF SIX SELECTIVE MEDIA FOR THE DETECTION AND ENUMERATION OF STAPHYLOCOCCUS AUREUS IN FOODS - ΑΛΜΠΑΛΑΣ, Β. (Journal of the Hellenic Veterinary Medical Society, 1974)
Six selective media for the detection and enumeration of coagulase-positive staphylococci werl ctudied evaluated for their efficiency in the recovery and easy recognition of five strains of Staphylococcus aureus. They were Mannitol Salt agar (MS', Tellurite Polymyxine Egg Yolk agar (TPEY),Egg Yolk Azide Agar (EYAA), Egg yolk Tellurite Glycine Pyruvate Agar (ETGPA). Milk Salt Agar (MSA), in combination with Salt Egg Yolk Agar (SEYA), and Vogel-Johnson agar (VJ), after enrichement in Trypticase Soy Broth 10V» NaCl.The recovery of the used strains was evaluated in pure cultures and after inoculation in various foods. None of the tested media was proved to be the ideal one. The media TPEY, ETGRA. and EYAA were considered as the nost appropriate for the detection of S. aureus in foods. The selective ability of eash medium is greatly depended on the strain and the food involved The simultaneoue use of two selective media is suggested if that is possible.